(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This paper proposes a numerical solution to the problem of symmetrical methane flow relative to the axis in infinite satellite flow and diffusion combustion. Dimensional equations in the Mises variables of the turbulent boundary layer of the interacting gases were used to model the object. The equations for the components of the gas mixture are reduced into one equation by introducing the Schwab-Zeldovich function. To solve the problem in the Mises coordinates, a two-layer four-point nonlinear boundary separation scheme was used, and a second order along the longitudinal coordinate was given. The iterative process was used because of the nonlinearity of the storage and displacement equations of substations. Individual results of the numerical experiment are presented.